Room-temperature continuous-wave topological Dirac-vortex microcavity lasers on silicon - Jingwen Ma; Taojie Zhou; Mingchu Tang; Haochuan Li; Zhan Zhang; Xiang Xi; Mickael Martin; Thierry Baron; Huiyun Liu; Zhaoyu Zhang; Siming Chen; Xiankai Sun (Light: Science & Applications, 2023)
Abstract Robust laser sources are a fundamental building block for contemporary information technologies. Originating from condensed-matter physics, the concept of topology has recently entered the realm of optics, offering fundamentally new design principles for lasers with enhanced robustness. In analogy to the well-known Majorana fermions in topological superconductors, Dirac-vortex states have recently been investigated in passive photonic systems and are now considered as a promising candidate for robust lasers. Here, we experimentally realize the topological Dirac-vortex microcavity lasers in InAs/InGaAs quantum-dot materials monolithically grown on a silicon substrate. We observe room-temperature continuous-wave linearly polarized vertical laser emission at a telecom wavelength. We confirm that the wavelength of the Dirac-vortex laser is topologically robust against variations in the cavity size, and its free spectral range defies the universal inverse scaling law with the cavity size. These lasers will play an important role in CMOS-compatible photonic and optoelectronic systems on a chip.